Ética, dignidade da mulher e da criança: reflexões sobre o aborto no Direito brasileiro - Sossai, Martha Angélica (2019)
This study aims to think about the legal reality of abortion in Brazil and its relationship with to ethics and the dignity of human person. A discussion is also made on the definitions about the beginning of human life that influenced the practice of abortion foreseen in the Brazilian legal system. In this sense, as the concept of the beginning of human life a controversial issue in the legal system, it is proclaimed in this study the possibility of achieving a reasonable measure to solve the contentious issue of abortion, which is divided between the right of unborn life and this dignity in counterpoint with the dignity of the human being of the woman, relating to the ethics part of the philosophical studies. Also it is reviewed the legal provisions that deal with abortion in Brazil, and the consequences that this act against life entails on people in an individual and collective ways, presenting the philosophical ethics as a guide for this study. Through a method of research of analysis and documentary and bibliographic study, the concept of life and its protection in the legal scope is defined; identified and described the types of abortion that are performed in Brazil